Proteomic analysis of whole-body responses in medaka (Oryzias latipes) exposed to benzalkonium chloride. Issue 12 (14th October 2020) - Kwon, Young Sang; Jung, Jae-Woong; Kim, Yeong Jin; Park, Chang-Beom; Shon, Jong Cheol; Kim, Jong-Hwan; Park, June-Woo; Kim, Sang Gon; Seo, Jong-Su
Abstract: Benzalkonium chloride (BAC) is a cationic surfactant commonly used as a disinfectant, and is discharged into the aquatic environment by various water sources such as wastewater. BAC may also interact with potentially toxic substances such as persistent organic chemicals. Although studies of BAC contamination toxicity and bioaccumulation have been widely reported, the biochemical responses to BAC toxicity remain incompletely understood, and the detailed molecular mechanisms are largely unknown. In this study, two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization tandem time-of-flight mass spectrometry-based proteomic approaches were applied to investigate the protein profiles in Oryzias latipes (medaka) chronically exposed to BAC. Fish were exposed to three different concentrations of BAC, 0.05, 0.1, and 0.2 mg/L, for 21 days. A total of 20 proteins involved in the cytoskeleton, the oxidative stress response, the nervous and endocrine systems, signaling pathways, and cellular proteolysis were significantly upregulated by BAC exposure. The proteomic information obtained in the present study will be useful in identification of potential biomarkers for BAC toxicity, and begins to elucidate its molecular mechanisms, providing new insights into the ecotoxicity of BAC.